Pengembangan Instrumen Kemampuan Berpikir Reflektif Matematis siswa Kelas 8 SMP - Muntazhimah, Muntazhimah (Universitas PGRI Semarang, 2019)
The Instrument is a measuring tools in a research. Before using the instrument, it must go through an analysis process to produce a good research instrument. This study aims to analyze the validity, reability and effectiveness of the test instruments for mathematical reflective thinking ability of 8th grade students’ of junior high schools by using research and development (RD). The stages in RD are: 1) needs analysis, 2) product design, 3) design and development, 4) expert validation, 5) preliminary product revision, 6) limited testing, 7) product revision, 8) expanded testing, 9) revision and analysis of the testing product. The result obtained indicate that the findings in this study are, the Instrument validity of each items indicates that the five items are valid, the reability of the instrument is 0,721 which shows good category and the effectiveness of the instrument there is a score of 76,7 which has a moderate level of effectiveness. This shows that the test instrument of mathematical reflective thinking ability of 8th grade students in valid, reliable and effective used to assess the mathematical reflective thinking ability of 8th grade students of junior high school.